The Effect of Online Trust and Repurchase Intention on Consumer Behavior in Online Shopping at E-Commerce - Golan Hasan; Silfia Nadilla Pattikawa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The purpose of this study was to determine the effect of Online Trust and Repurchase Intention on consumer behavior in Online Shopping at E-Commerce. This study investigates five factors; Perceived Risk, Perceived Usefulness, Website Appearance, Online Promotion, Security. The data collections technique was carried out using a questionnaire and distributed through online social media. This study used 356 respondents. Data was analyzed using PLS-SEM. The results of this study shown that Perceived Risk, Website Appearance, Security, and Online Promotion has a significant relationship to Online Trust. Perceived Usefulness had a negative effects on Online Trust. This study also confirm that Perceived Risk, Perceived Usefulness, Website Appearance, Security, and Online Promotion has a positive impact on Repurchase Intention. Lastly, Online Trust influences Repurchase Intention in E-Commerce.